A wear-resistant workpiece and a method for manufacturing the same
Patent Information
- Application Number
- CN202611213429.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-13
AI Technical Summary
为了满足厚度需求,通常仅进行单层堆焊,这会导致碳化铬覆盖层内碳化铬颗粒浓度下降,耐磨性和硬度均难以满足使用要求
[0015]根据本发明的第一方面,以激光作为热源进行堆焊,并采用较高的激光功率和焊接速度,有助于减小熔池,并控制输入母材的中能量,从而降低熔深,降低稀释率,保证硬面层内碳化铬硬质颗粒的含量,提高硬面层的硬度和耐磨性能。通过配合激光功率约束焊接速度、送丝速度,有助于形成厚度适中的首层硬面层,便于形成硬面层厚度较小且耐磨性能较好的耐磨工件。通过使药芯焊丝的端部深入熔池中部,使激光的能量先传递至药芯焊丝,再传递至母材,使热量主要集中于药芯焊丝,便于减小母材的熔深,并保证药芯焊丝充分熔融,有助于保证焊接质量,并降低稀释率,提高硬面层的硬度和耐磨性。
Smart Images

Figure CN122895697A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of surfacing technology, and in particular to a wear-resistant workpiece and its preparation method. Background Technology
[0002] Chromium carbide overlay (CCO) possesses good wear resistance and high hardness. It is typically formed on the surface of a base material through welding, serving to protect the base material. It is currently widely used in cement, mining, steel, and power industries. During the welding process, part of the base material and the flux-cored wire melt simultaneously to form a molten pool. The molten pool cools and solidifies, forming a CCO overlay containing a large number of hard chromium carbide particles. When the base material content in the molten pool is high, i.e., the dilution rate is high, the concentration of chromium carbide particles in the CCO overlay decreases, leading to a reduction in hardness and wear resistance. To ensure the wear resistance and hardness of the CCO overlay, multi-layer welding is usually performed to reduce the overall dilution rate, resulting in a higher total thickness of the CCO overlay.
[0003] In actual production, to meet product structural requirements, a relatively thin chromium carbide coating is often needed. To meet these thickness requirements, a single-layer welding process is typically performed, which leads to a decrease in the concentration of chromium carbide particles within the coating, making it difficult to meet the required wear resistance and hardness. While this can be compensated for by adding various alloy and non-alloy powder composites to supplement other types of hard particles and improve the hardness and wear resistance of the alloy matrix, the formulation of such flux-cored welding wires is difficult to prepare and costly, and there is still a risk of burn-through when the base material thickness is small, hindering its widespread application. Summary of the Invention
[0004] The purpose of this invention is to provide a wear-resistant workpiece with a small hard surface layer thickness and high wear resistance, and a method for preparing the same.
[0005] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a wear-resistant workpiece includes: using a laser as a heat source and a flux-cored welding wire as a solder to deposit a hardened layer on the surface of a base material, wherein the flux-cored welding wire comprises Cr and C elements, and during the depositing process, the end of the flux-cored welding wire projected onto the base material penetrates into the molten pool, wherein the power of the laser is any value between 3.5kW and 5kW, the welding speed is any value between 1250mm / min and 1650mm / min, the wire feeding speed of the flux-cored welding wire is any value between 2m / min and 4m / min, and the thickness of the first layer of the deposited layer is any value between 1mm and 3mm.
[0006] Optionally, the flux-cored wire includes a filler and an outer sheath enclosing the filler. The outer sheath is a low-carbon steel strip. The Cr content in the filler is any value between 50wt% and 70wt%, the C content is any value between 6wt% and 9wt%, and the filling rate of the flux-cored wire is any value between 35% and 60%.
[0007] Optionally, the filler is high-carbon ferrochrome powder, and the flux-cored wire is melted under a protective atmosphere.
[0008] Optionally, the equivalent spot size of the laser can be set to any value between 5.5 mm and 6.5 mm.
[0009] Optionally, the welding method is a single layer with multiple passes, and the weld overlap rate is set to any value between 50% and 60%, and the dilution rate is set to any value between 3% and 10%.
[0010] Optionally, the base material is made of low-carbon steel.
[0011] Optionally, the base material is plate-shaped and has a thickness of 1.5 mm or more.
[0012] Optionally, the projection of the flux-cored wire onto the base material extends through the molten pool.
[0013] Secondly, the present invention also provides a wear-resistant workpiece, which is prepared by the above-described method for preparing a wear-resistant workpiece, wherein the content of Cr element in the hard surface layer is any value between 20wt% and 40wt%, and the content of C element is any value between 2.5wt% and 5.5wt%.
[0014] Optionally, the hardened layer further includes Si and Mn elements, wherein the Si content in the hardened layer is any value between 0.2wt% and 2wt%, and the Mn content is any value between 0.2wt% and 2wt%.
[0015] According to a first aspect of the invention, using a laser as a heat source for surfacing welding, and employing high laser power and welding speed, helps to reduce the molten pool and control the medium energy input to the base material, thereby reducing the penetration depth, reducing the dilution rate, ensuring the content of chromium carbide hard particles in the hardened layer, and improving the hardness and wear resistance of the hardened layer. By coordinating the laser power to constrain the welding speed and wire feed speed, it helps to form a first hardened layer of moderate thickness, facilitating the formation of wear-resistant workpieces with a relatively small hardened layer thickness and good wear resistance. By extending the end of the flux-cored wire deep into the center of the molten pool, the laser energy is first transferred to the flux-cored wire and then to the base material, so that the heat is mainly concentrated on the flux-cored wire, which helps to reduce the penetration depth of the base material and ensures that the flux-cored wire is fully melted, thus helping to ensure welding quality, reduce the dilution rate, and improve the hardness and wear resistance of the hardened layer.
[0016] According to a second aspect of the present invention, a high-carbon, high-chromium hardfacing layer prepared by a low-dilution welding method has high hardness and wear resistance, effectively protecting the base material and extending the service life of wear-resistant workpieces.
[0017] The above description is merely an overview of the technical solution of the present invention. In order to better understand the technical means of the present invention and to implement it in accordance with the contents of the specification, the preferred embodiments of the present invention are described in detail below with reference to the accompanying drawings. Attached Figure Description
[0018] Figure 1 This is a schematic diagram of the method for preparing wear-resistant workpieces as shown in Embodiment 1 of the present invention.
[0019] Legend: 1-Base material, 2-Fluorescent wire, 21-Outer sheath, 22-Fill, 3-Molten pool, 4-Laser welding head, 5-Wire feeder, 61-Base layer, 62-Hard surface layer. Detailed Implementation
[0020] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0021] In the description of this invention, it should be noted that the terms "center," "upper," "lower," "left," "right," "vertical," "horizontal," "inner," and "outer," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are used only for the convenience of describing the invention and for simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the invention. Furthermore, the terms "first," "second," and "third" are used for descriptive purposes only and should not be construed as indicating or implying relative importance.
[0022] In the description of this invention, it should be noted that, unless otherwise explicitly specified and limited, the terms "installation," "connection," and "linking" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal connection of two components. Those skilled in the art can understand the specific meaning of the above terms in this invention based on the specific circumstances.
[0023] Furthermore, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0024] This invention claims a method for preparing a wear-resistant workpiece, comprising: using a laser as a heat source and a flux-cored welding wire 2 as a solder to deposit a hardened layer 62 on the surface of a base material 1, thereby obtaining a hardened layer 62. The flux-cored welding wire 2 comprises Cr and C elements, and during the depositing process, the end of the flux-cored welding wire 2 projected onto the base material 1 penetrates into the molten pool 3. The laser power is any value from 3.5kW to 5kW, for example, any value from 3.5kW, 4kW, 4.5kW, and 5kW. The welding speed is any value from 1250mm / min to 1650mm / min, for example, any value from 1250mm / min, 1350mm / min, 1400mm / min, 1450mm / min, 1500mm / min, 1550mm / min, 1600mm / min, and 1650mm / min. The wire feed speed of the flux-cored welding wire 2 is any value between 2m / min and 4m / min, for example, any value among 2m / min, 2.5m / min, 3m / min, 3.5m / min, and 4m / min. The thickness of the first layer of the weld overlay is any value between 1mm and 3mm, for example, any value among 1mm, 1.5mm, 2mm, 2.5mm, and 3mm.
[0025] Lasers offer advantages such as high energy density and precise heat input control. Using a laser as a heat source for surfacing welding, along with higher laser power and welding speed, helps reduce the molten pool 3 and control the medium energy input to the base material 1, thereby reducing the penetration depth and dilution rate. This ensures the content of chromium carbide hard particles within the hardened layer 62, improving its hardness and wear resistance. By coordinating laser power with welding speed and wire feed speed, it helps form a first hardened layer 62 of moderate thickness, facilitating the formation of wear-resistant workpieces with a relatively thin hardened layer 62 and good wear resistance. By extending the end of the flux-cored wire 2 into the center of the molten pool 3, the laser energy is first transferred to the flux-cored wire 2 and then to the base material 1, concentrating the heat primarily on the flux-cored wire 2. This helps reduce the penetration depth of the base material 1 and ensures the flux-cored wire 2 is fully melted, contributing to weld quality, reducing dilution rate, and improving the hardness and wear resistance of the hardened layer 62.
[0026] In some embodiments, the flux-cored wire 2 includes a filler 22 and an outer sheath 21 enclosing the filler 22. The outer sheath 21 is a low-carbon steel strip. The Cr content in the filler 22 is any value from 50wt% to 70wt%, for example, any value from 50wt%, 55wt%, 60wt%, 65wt%, and 70wt%, preferably any value from 65wt% to 70wt%. The C content is any value from 6wt% to 9wt%, for example, any value from 6wt%, 7wt%, 8wt%, and 9wt%, preferably any value from 8wt% to 9wt%. The filling rate of the flux-cored wire 2 is any value from 35% to 60%, for example, any value from 35%, 40%, 50%, and 60%, preferably any value from 45% to 55%.
[0027] The high content of carbon and chromium in the filler 22 of the flux-cored wire 2 helps to make the composition of the hardening layer 62 close to that of the classic chromium carbide coating layer, so as to ensure the hardness, wear resistance and corrosion resistance of the hardening layer 62.
[0028] In some embodiments, the filler 22 is high-carbon ferrochrome powder, which is melted in a protective atmosphere by the flux-cored wire 2. High-carbon ferrochrome powder is a commonly used component of flux-cored wire 2, readily available, and its elemental ratio meets the component requirements. Balanced welding parameters ensure the stability of the molten pool 3. Due to the small thickness of the single-layer weld, the cooling rate is high, facilitating the formation of isolated, dispersed granular carbides, thus achieving grain refinement. Therefore, there is no need to add other alloying elements that promote grain refinement and adjust the stability of the molten pool 3, such as molybdenum, niobium, vanadium, tungsten, boron, etc. Forming the filler 22 of the flux-cored wire 2 with a single component helps simplify the preparation operation of the flux-cored wire 2 and improve preparation efficiency.
[0029] In some embodiments, the equivalent spot size of the laser is set to any value between 5.5 mm and 6.5 mm, for example, any value among 5.5 mm, 6 mm, and 6.5 mm. A larger equivalent spot size prevents excessive heat concentration leading to excessive melting depth, and helps reduce the dilution rate while ensuring the stability of the molten pool 3.
[0030] In some embodiments, the welding method is a single layer with multiple passes, and the weld overlap rate is set to any value between 50% and 60%, for example, any value between 50%, 55%, and 60%, to facilitate the formation of a flat and uniform hard surface layer 62. The dilution rate is any value between 3% and 10%, for example, any value between 3%, 5%, and 10%.
[0031] In some embodiments, the base material 1 is made of low-carbon steel.
[0032] In some embodiments, the base material 1 is constructed as a plate and has a thickness of any value greater than or equal to 1.5 mm, such as any value among 1.5 mm, 2 mm, 2.5 mm, 5 mm, 6 mm, and 12 mm. Because the weld penetration is relatively low, it is suitable for base materials with smaller thicknesses and is less prone to problems such as burn-through.
[0033] In some embodiments, the projection of the flux-cored wire 2 onto the base material 1 penetrates the molten pool 3, which facilitates the melting of the flux-cored wire 2, reduces the heat input to the base material 1 by the laser, reduces the melting depth, reduces the dilution rate, reduces the thickness of the hardened layer 62, and ensures the mechanical properties of the hardened layer 62.
[0034] Secondly, the present invention also provides a wear-resistant workpiece, prepared by the above-described method for preparing a wear-resistant workpiece, wherein the Cr content in the hardened layer 62 is any value from 20wt% to 40wt%, for example, any value from 20wt%, 25wt%, 30wt%, 35wt%, and 40wt%, preferably any value from 28wt% to 36wt%. The C content is any value from 2.5wt% to 5.5wt%, for example, any value from 2.5wt%, 3.5wt%, 4.5wt%, and 5.5wt%, preferably any value from 3.0wt% to 4.5wt%.
[0035] The high-carbon, high-chromium hardened layer 62, prepared by a low-dilution welding method, has high hardness and wear resistance, effectively protecting the base material 1 and extending the service life of wear-resistant workpieces.
[0036] In some embodiments, the hardened layer 62 further includes Si and Mn elements. The Si content in the hardened layer 62 is any value from 0.2wt% to 2wt%, for example, any value from 0.2wt%, 0.8wt%, 1.0wt%, 1.4wt%, and 2wt%, preferably any value from 3.0wt% to 4.5wt%. The Mn content is any value from 0.2wt% to 2wt%, for example, any value from 0.2wt%, 0.6wt%, 0.8wt%, 0.9wt%, 1.4wt%, and 2wt%, preferably any value from 0.3wt% to 1.2wt%.
[0037] Please refer to the following examples for details.
[0038] Example 1: Please see Figure 1 The preferred embodiment of this application shows a method for preparing a wear-resistant workpiece, which includes: Using a laser as a heat source and flux-cored welding wire 2 as a solder, a hardened layer 62 is obtained by overlaying on the surface of the base material 1.
[0039] In this embodiment, a laser beam, perpendicular to the surface of the base material 1, is emitted from the laser welding head 4 to melt a portion of the material on the surface of the base material 1 and the corresponding portion of the flux-cored wire 2, forming a molten pool 3. The wire feeder 5 automatically feeds the wire in a pre-feeding manner, delivering the end of the flux-cored wire 2 to the center and trailing edge of the molten pool 3, ensuring that the end of the flux-cored wire 2 projected onto the base material 1 penetrates deep into the molten pool 3. Argon gas is used as the shielding gas during welding. In some embodiments, the end of the flux-cored wire 2 corresponds to the trailing edge of the molten pool 3, so that the projection of the flux-cored wire 2 onto the base material 1 penetrates the molten pool 3.
[0040] The base material 1 is made of SS400 low carbon steel plate with a thickness of 2.0 mm. Its surface is treated by sandblasting to remove rust before welding, so that the surface of the base material 1 to be welded is clean and relatively flat.
[0041] The flux-cored welding wire 2 consists of an outer sheath 21 and a filler 22. The outer sheath 21 is made of low-carbon steel, and the filler 22 consists of only one component: high-carbon ferrochrome powder. The filler 22 contains 68% Cr and 8.5% C. The overall diameter of the flux-cored welding wire 2 is 2.0 mm.
[0042] During the welding process, the laser power was 4.0kW, the equivalent spot size was 6mm, the welding speed was 1500mm / min, the wire feed speed was 3m / min, the welding method was one layer with multiple passes, the weld overlap rate was 55%, and a hard surface layer 62 was obtained after curing.
[0043] In existing conventional methods, the laser power is usually set in the range of 2.8kW to 3.5kW, so that the end of the flux-cored wire 2 corresponds to the leading edge of the molten pool 3, and the welding speed is set in the range of 150mm / min to 450mm / min. The ratio of wire feed speed to welding speed is usually in the range of 0.0052 to 0.0065, and the equivalent spot size is usually in the range of 1.0mm to 3.5mm.
[0044] Compared with the prior art, the parameters in this embodiment are all significantly deviated. This is to cooperate with the special base material 1 and flux-cored wire 2 in this embodiment to obtain a hardened layer 62 with a specific structure.
[0045] During welding, the temperature gradient at the leading edge of the molten pool 3 is the largest and the temperature is relatively low. The high-carbon ferrochrome flux-cored wire 2 contains a large number of high-melting-point high-carbon ferrochrome particles. To prevent incomplete melting of the alloy particles within the flux core and the generation of unmelted hard inclusions, the end of the flux-cored wire 2 is inserted deep into the high-temperature interior of the molten pool 3. This ensures complete melting of the high-carbon ferrochrome particles and helps suppress thermal fluctuations within the molten pool 3, improving its stability. Because the flux-cored wire 2 penetrates deep into the molten pool 3, it becomes interposed between the portion of the base material 1 corresponding to the molten pool 3 and the laser welding head 4, creating an obstruction problem. To suppress the heat input problem to the substrate caused by this obstruction, this embodiment uses a larger equivalent spot size than usual to compensate for insufficient heat input due to laser obstruction. This also reduces the surface temperature of the base material 1, decreases the penetration depth, and lowers the risk of burn-through. Increasing the equivalent spot size also helps to expand the molten pool 3, thereby reducing the thickness of the hardened layer 62 and facilitating the formation of a thinner hardened layer 62. Using a high-power laser helps ensure the flux-cored wire 2 melts fully and compensates for heat dispersion caused by the expansion of the molten pool 3. Using a high welding speed, coupled with a high wire feed speed, helps reduce the risk of the high-power laser burning through the base material 1 and contributes to the formation of a uniform, stable, and tightly bonded hardened layer 62. In this application, by employing unconventional welding methods and parameters, the dilution rate of the base material 1 during welding is reduced, resulting in the stable formation of a thinner hardened layer 62 with higher hardness and wear resistance.
[0046] This application overcomes the biases of feeding the end of the flux-cored wire 2 to the leading edge of the molten pool 3 and common technical parameters, in order to stably form a hardened layer 62 with a relatively small thickness and containing a large number of chromium carbide hard particles. In this application, feeding the end of the flux-cored wire 2 into the molten pool 3 and the selection of various welding parameters are interrelated and indispensable, constituting a complete technical solution and should not be viewed separately.
[0047] The wear-resistant workpiece obtained in this embodiment includes a substrate layer 61 and a hardening layer 62 that are stacked and interconnected. The substrate layer 61 is transformed from the base material 1. Cutting the wear-resistant workpiece and observing its cross-section using a metallographic microscope reveals that the alloy substrate structure of the hardening layer 62 is uniform and refined, with densely distributed and uniformly sized hard particles. Analysis shows that the thickness of the hardening layer 62 is approximately 2.2 mm, and the dilution rate during welding is approximately 3.8%.
[0048] Analysis of the hardening layer 62 revealed that it contains 32.72% Cr, 3.46% C, 0.85% Si, and 0.66% Mn. The hardness of the hardening layer 62 was measured to be 60.6 HRC. The abrasion resistance of the hardening layer 62 was tested using Procedure A of ASTM G65-2016, "Standard Test Method for Determining the Abrasion Resistance of Metals and Materials Using a Dry Sand / Rubber Wheel Apparatus," and the abrasion loss was measured to be 0.174 g. The same method was used to test the abrasion loss of a classic 4.5% C-25% Cr chromium carbide coating, which was 0.17 g, indicating that the abrasion-resistant layer in this embodiment exhibits good abrasion resistance.
[0049] Based on the actual measured dilution rate and hardening layer 62 composition, as well as the elemental composition of flux-cored wire 2 and base material 1, the elemental transition coefficient of carbon was calculated to be as high as 84.4%, indicating that the metallurgical burn-off rate during the welding process is reasonable. It also proves that although there is extremely high energy in the laser-formed molten pool 3, the carbon burn-off was successfully reduced through the tight process parameter control, making it sufficient to combine with chromium elements and precipitate a large amount of high-hardness chromium carbides, i.e., hard particles, in the extremely thin hardening layer 62.
[0050] Example 2: The only difference between this embodiment and Embodiment 1 is that the welding speed is set to 1350 mm / min, the wire feed speed to 3.4 m / min, and the welding method to be two layers and multiple passes. The thickness of the first layer was measured to be 2.4 mm, and the total thickness to be 5.6 mm. The composition of the hardening layer 62 was analyzed, revealing a Cr content of 34.51% and a C content of 3.99%. The mechanical properties of the hardening layer 62 were also analyzed, showing a hardness of 61.0 HRC and a wear rate of 0.169 g.
[0051] Example 3: The only difference between this embodiment and Embodiment 1 is that the wire feed speed is set to 3.6 m / min, the equivalent spot size is 5.5 mm, the welding method is two layers and multiple passes, and the welding overlap rate is 50%. The thickness of the first layer was measured to be 2.3 mm, and the total thickness was 5.2 mm. The composition of the hardening layer 62 was analyzed, revealing a Cr content of 34.31% and a C content of 4.02%. The mechanical properties of the hardening layer 62 were also analyzed, showing a hardness of 59.7 HRC and a wear rate of 0.188 g.
[0052] Example 4: The only difference between this embodiment and Embodiment 1 is that the welding speed is set to 1300 mm / min, the wire feed speed to 3.6 m / min, and the welding method to be three layers and multiple passes. The thickness of the first layer was measured to be 2.5 mm, and the total thickness to be 9.1 mm. The composition of the hardening layer 62 was tested, revealing a Cr content of 35.73% and a C content of 4.25%. The mechanical properties of the hardening layer 62 were tested, showing a hardness of 59.2 HRC and a wear loss of 0.151 g. Compared to Embodiment 1, the hardness of the hardening layer 62 in this embodiment is slightly lower. This is because the hardening layer 62 contains a large number of coarse chromium carbide particles, which are prone to breakage, resulting in a slight decrease in the hardness value. The decrease has little impact on the practical application of the hardening layer 62. Furthermore, when testing wear resistance, due to the relatively low stress, the larger chromium carbide particles still exhibit high wear resistance.
[0053] The beneficial effect of this invention is that it provides a method for stably obtaining a thin hardened layer 62 with a relatively small thickness and high wear resistance. By feeding the flux-cored wire 2 into the leading edge or near the center of the laser-formed molten pool 3, the laser energy preferentially melts the flux-cored wire 2 and its high-carbon ferrochrome powder filler 22. At the same time, the laser power, travel speed, wire feed speed, spot size, focal position, and overlap rate are controlled to maintain the process in a "cladding mode" rather than a "deep penetration welding mode," limiting the penetration depth so that the molten flux-cored wire 2 component occupies the main proportion of the molten pool 3, and the base material 1 only provides a small amount of surface molten layer, thereby reducing the dilution rate of the base material 1 and avoiding deep penetration or keyhole effect.
[0054] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0055] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A method for preparing a wear-resistant workpiece, characterized in that, include: Using a laser as a heat source and a flux-cored wire (2) as a solder, a hardened layer (62) is deposited on the surface of the base material (1) to obtain a hardened layer (62). The flux-cored wire (2) includes Cr and C elements. During the depositing process, the end of the flux-cored wire (2) projected onto the base material (1) penetrates into the molten pool (3). The power of the laser is any value between 3.5kW and 5kW, the welding speed is any value between 1250mm / min and 1650mm / min, the wire feeding speed of the flux-cored wire (2) is any value between 2m / min and 4m / min, and the thickness of the first layer of the deposited layer is any value between 1mm and 3mm.
2. The method for preparing wear-resistant workpieces as described in claim 1, characterized in that, The flux-cored wire (2) includes a filler (22) and an outer sheath (21) that wraps the filler (22). The outer sheath (21) is a low-carbon steel strip. The Cr content in the filler (22) is any value between 50wt% and 70wt%, the C content is any value between 6wt% and 9wt%, and the filling rate of the flux-cored wire (2) is any value between 35% and 60%.
3. The method for preparing wear-resistant workpieces as described in claim 2, characterized in that, The filler (22) is high carbon ferrochrome powder, and the flux-cored wire (2) is melted under a protective atmosphere.
4. The method for preparing wear-resistant workpieces as described in claim 1, characterized in that, The equivalent spot size of the laser is set to any value between 5.5 mm and 6.5 mm.
5. The method for preparing wear-resistant workpieces as described in claim 1, characterized in that, The welding method is a single layer with multiple passes, with the weld overlap rate set to any value between 50% and 60%, and the dilution rate set to any value between 3% and 10%.
6. The method for preparing wear-resistant workpieces as described in claim 1, characterized in that, The material of the base material (1) is low carbon steel.
7. The method for preparing wear-resistant workpieces as described in claim 1, characterized in that, The base material (1) is plate-shaped and has a thickness of any value greater than or equal to 1.5 mm.
8. The method for preparing wear-resistant workpieces as described in claim 1, characterized in that, The projection of the flux-cored wire (2) onto the base material (1) penetrates the molten pool (3).
9. A wear-resistant workpiece, characterized in that, The wear-resistant workpiece is prepared by the method described in any one of claims 1 to 8, wherein the content of Cr element in the hard surface layer (62) is any value between 20wt% and 40wt%, and the content of C element is any value between 2.5wt% and 5.5wt%.
10. The wear-resistant workpiece as described in claim 9, characterized in that, The hardened layer (62) also includes Si and Mn elements. The content of the Si element in the hardened layer (62) is any value between 0.2wt% and 2wt%, and the content of the Mn element is any value between 0.2wt% and 2wt%.